Native Wildflowers: Container Production of Joe-Pye Weed From Seed - Jeffrey G. Norcini; James H. Aldrich; Gale Allbritton (EDIS)
In this publication, we describe a production protocol that results in Joe-Pye weed plants that are only 18 to 24 inches tall when they are ready to ship. This document is ENH876, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2003.